Hubungan antara Kecemasan dengan Kejadian Preeklampsia Di Kabupaten Banyumas Jawa Tengah - Adi Isworo, M. Hakimi, Trisno Agung Wibowo (Berita Kedokteran Masyarakat (BKM), 2012)
Background: Preeclampsia or eclampsia is a collection of symptoms that can occur in pregnant women, women in labor, and in the puerperium phase, characterized by hypertension and proteinuria. The condition is sometimes accompanied by convulsions to coma, called eclampsia. The direct cause of maternal mortality rate (MMR) is bleeding (30%), eclampsia (25%), parturition time (5%), abortion complications (8%), and infections (12%). National maternal mortality rate in 2007 was 228/100.000 live births. MMR in Central Java in 2008 was 114.42 / 100,000. Banyumas, one of regencies in Central Java has the highest total fertility rate (2.31). MMR in 2009 was 41 cases due to cause’s preeclampsia/eclampsia, 9 cases (22%).Methods: Case-control, located in Banyumas. Subjects in this study drawn from the study population by accidental sampling; those are pregnant women who were diagnosed as preeclampsia. The sample consisted of 276 pregnant women (138 cases and 138 controls). Measurement of risk factors (anxiety) used a questionnaire T-MAS. Estimated magnitude of the risk factors determined by the odds ratio (OR) stratified by previous test and multivariate analysis to control the confounder.Results: 59 (42.8%) experienced anxiety. The results of bivariate analysis between the main variables of anxiety with the incidence of preeclampsia in pregnant women shown OR=7.84; (CI=3.967-15.501); p<0.01. Then, the results of bivariate analysis of external variables with preeclampsia: a history of preeclampsia OR=19.24; (CI:2.524-146.246); p<0.01, a history of descendants of preeclampsia OR=8.52 (CI=2.903-25.049);p<0.01, history of hypertension OR=12.50; (CI=3.714-42.065); p<0.01, and the history of the ANC OR=3.00; (CI=1.560-5.784); P<0.01. From the stratified analysis, a history of hypertension is a confounder with the difference of OR=24.2%. There are an interaction between anxiety and a history of preeclampsia, hypertension and offspring with the incidence of preeclampsia. The results of multivariate analysis of anxiety showed OR=11.36; (CI=5.400-23.902); p<0.01, a history of preeclampsia OR=11.050; (CI=1.285-95.057); p=0.02, a history of descendants of preeclampsia OR=8.46; (CI=2.636-27.200); p<0.01; history of hypertension OR=10.50; (CI=2.834-38.958); p<0.01, and the history of the ANC: OR=2.75; (CI=1.209-6.274), p=0.01. Equation model 3 can be accepted: Preeclampsia = -1,958 + 2,430 (anxiety) + 2,402 (history of preeclampsia) + 2,136 (history of descendants of preeclampsia) + 2,352 (history of hypertension) + 1,013 (history of the ANC)Conclusion: Anxiety associated with the occurrence of preeclampsia. History of hypertension is a confounding variable. Furthermore, a history of preeclampsia, hypertension and history of descendants of preeclampsia are the giver of the effect of modification. In the multivariate analysis of main variables and external variables related to the incidence of preeclampsia is anxiety, a history of preeclampsia, history of descendants of preeclampsia, a history of hypertension and history of the ANC.Keywords: preeclampsia, anxiety, T-Mas (Taylor Manifest Anxiety Scale)